2015
DOI: 10.1097/sap.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Pulsed Electromagnetic Field Stimulation on Platelet-Rich Plasma and Bone Marrow Stromal Stem Cell Using Rat Zygomatic Bone Defect Model

Abstract: It was observed that the superficial temporal fascial flap used in the experiment was a good scaffold choice, providing an ideal bone regeneration area because of its autogenous, vascular, and 3-dimensional structures. As a result, it is presumed that this combination in the nonhealing bone defects is a rather useful treatment choice and can be used in a reliable way in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Osteopontin scoring was higher in the bone group, which correlates with the study by Kapi et al 34 Other histological parameters were similar and correlated with 2 previous studies, 11,31 but no evaluation of electron microscopy was performed in either study. According to the SEM results, Ca/P ratios were similar, and there was no significant difference between the ratios stated in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Osteopontin scoring was higher in the bone group, which correlates with the study by Kapi et al 34 Other histological parameters were similar and correlated with 2 previous studies, 11,31 but no evaluation of electron microscopy was performed in either study. According to the SEM results, Ca/P ratios were similar, and there was no significant difference between the ratios stated in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, an animal study demonstrated that PEMFs could enhance angiogenesis in both normal mice and diabetic mice [ 53 ]. Interestingly, the effect of PEMFs on platelet rich plasma mediates a beneficial and effective combination in terms of bone regeneration [ 54 ]. In fibroblast-like cells derived from mononuclear peripheral blood cells, PEMF irradiation protocol decreased some of the most important proinflammatory cytokine secretion such as TNF- α and IL-1 β and a significant increase in cytokines of lymphocytic origin such as IL-10 [ 55 ].…”
Section: Effect Of Low Frequency Low Energy Pulsed Electromagneticmentioning
confidence: 99%
“…Conventional methods include conservative exercise and orthosis intervention. Although there is certain effect, most patients are still difficult to recover in time after conventional treatment [7] . PRP is gained through autoblood sample treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After the completion of treatment, conventional treatment was done for the patient's wound, and the orthosis was used to fix. In a short time, walking with load would not be implemented [4] . After 3M, the treatment conditions of both groups were reexamined.…”
Section: Methodsmentioning
confidence: 99%